An altered transcriptome underlies cln5-deficiency phenotypes in Dictyostelium discoideum - Kim, William D.; Huber, Robert J. (Frontiers in Genetics, 2022)
Mutations in CLN5 cause a subtype of neuronal ceroid lipofuscinosis (NCL) called CLN5 disease. The NCLs, commonly known as Batten disease, are a family of neurodegenerative lysosomal storage diseases that affect all ages and ethnicities globally. Previous research showed that CLN5 participates in a variety of cellular processes. However, the precise function of CLN5 in the cell and the pathway(s) regulating its function are not well understood. In the model organism Dictyostelium discoideum, loss of the CLN5 homolog, cln5, impacts various cellular and developmental processes including cell proliferation, cytokinesis, aggregation, cell adhesion, and terminal differentiation. In this study, we used comparative transcriptomics to identify differentially expressed genes underlying cln5-deficiency phenotypes during growth and the early stages of multicellular development. During growth, genes associated with protein ubiquitination/deubiquitination, cell cycle progression, and proteasomal degradation were affected, while genes linked to protein and carbohydrate catabolism were affected during early development. We followed up this analysis by showing that loss of cln5 alters the intracellular and extracellular amounts of proliferation repressors during growth and increases the extracellular amount of conditioned medium factor, which regulates cAMP signalling during the early stages of development. Additionally, cln5- cells displayed increased intracellular and extracellular amounts of discoidin, which is involved in cell-substrate adhesion and migration. Previous work in mammalian models reported altered lysosomal enzyme activity due to mutation or loss of CLN5. Here, we detected altered intracellular activities of various carbohydrate enzymes and cathepsins during cln5- growth and starvation. Notably, cln5- cells displayed reduced β-hexosaminidase activity, which aligns with previous work that showed that D. discoideum Cln5 and human CLN5 can cleave the substrate acted upon by β-hexosaminidase. Finally, consistent with the differential expression of genes associated with proteasomal degradation in cln5- cells, we also observed elevated amounts of one of the proteasomal subunits and reduced proteasomal activity during cln5- growth and starvation. Overall, this study reveals the impact of cln5-deficiency on gene expression in D. discoideum, provides insight on the genes and proteins that play a role in regulating Cln5-dependent processes, and sheds light on the molecular mechanisms underlying CLN5 disease.